Strategies to Overcome the Limitations of AIEgens in Biomedical Applications. Issue 9 (30th April 2018) - Gu, Bobo; Yong, Ken‐Tye; Liu, Bin
Abstract: Motivated by the demand for high‐performance tools for biomedical applications, numerous new luminescent nanomaterials with advanced functionalities are synthesized in recent years. Conventional fluorophores generally suffer from the notorious aggregation‐caused quenching effect that deteriorates their practical performance. The recently emerged fluorogens with aggregation‐induced emission (AIE) characteristics (AIEgen) have generated a new avenue for biomedical applications due to their unique optical properties, flexible designability, and multifunctional potential. However, the inherent characteristics of AIEgens, including short wavelength absorption, broad emission, and aggregation‐dependent brightness indirectly limit their practical performance in the biomedical field. Here, the recent development of AIEgens for biomedical applications is summarized and novel strategies to overcome their limitations are proposed. Furthermore, the strategies and guidelines for the rational design of AIEgens, preparation of water‐dispersible AIE nanoparticles, and selection of the excitation/emission methods, which enable AIEgens to be useful in a broader range of biomedical applications, are discussed. Abstract : Fluorogens with an aggregation‐induced emission (AIE) feature, which have recently emerged, open up a new avenue for biomedical applications. However, the inherent spectral characteristics of the AIE materials limit their practical performance. The recently developed strategies to overcome these limitations are summarized and analyzed with future perspective discussed.